MENINGKATKAN PENGETAHUAN PASIEN HIPERTENSI TENTANG PENCEGAHAN STROKE: PERBANDINGAN ANTARA TEMUAN EMPIRIS DAN TINJAUAN SISTEMATIS - Ilhamsyah, Rudi; Prabaningtyas, Hanindia Riani; Yang, Han (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2025)
Abstract Background Stroke is leading cause of morbidity and mortality globally, particularly in developing countries where hypertension is a significant modifiable risk factor. The awareness of stroke risk factors among hypertensive patients crucial for effective prevention strategies. Hypertension is recognized as primary risk factor for stroke, contributing to approximately 70% of ischemic strokes globally. In Indonesia, the prevalence of hypertension is high, with studies indicating that 33.4% of individuals aged 43.3 years are affected, underscores the urgent need for enhanced awareness and education regarding stroke prevention. Research Objectives The primary objective of this research is to enhance knowledge of hypertensive patients regarding stroke prevention through two approaches: empirical study in Karanggeneng, Boyolali, and systematic review. Methods and Materials This study combining an empirical study conducted in Karanggeneng, Boyolali, with systematic review registered in PROSPERO (ID: CRD420251011016). The empirical study utilized pre and post-test design. Statistical analysis performed using Wilcoxon Signed Ranks Test. Results The empirical study revealed improved knowledge scores. Wilcoxon Signed Ranks Test yielded a Z value of -5.563 with an asymptotic significance <0.001, indicating a statistically significant increase in knowledge. The review reported improvements in knowledge following educational interventions, there were still notable gaps in awareness regarding stroke risk factors and prevention strategies. Conclusion This research underscores importance of educational intervention enhancing stroke knowledge. The findings from both the empirical study and the systematic review suggest that continuous education and awareness programs are essential for improving health outcomes, reducing the risk of stroke. Keywords: Stroke, Hypertension, Knowledge, Educational Intervention